A preparation method and application of hierarchical porous cobalt hydroxide nanodisks

Hierarchical porous Co(OH)2 nanodisks were prepared by using cobalt oxide salts and calcium methoxide templates in methanol solution through a heterogeneous synthesis method, which solved the problem of efficient utilization of biomass materials and the development of two-dimensional transition metal hydroxide nanomaterials. Heterogeneous preparation problems have been achieved to achieve efficient degradation of organic pollutants.

CN116395755BActive Publication Date: 2025-01-21FUZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310404379.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-17
Publication Date
2025-01-21
Estimated Expiration
2043-04-17

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently utilize biomass materials such as discarded egg shells and oyster shells, and two-dimensional transition metal hydroxide nanomaterials are mainly prepared under homogeneous conditions, and there is a lack of preparation methods under heterogeneous conditions.

Method used

Using a heterogeneous synthesis method, using calcium oxide as a precursor, hierarchical porous Co(OH)2 nanodisks were prepared through magnetic stirring and ion exchange reaction in methanol solution. The method includes mixing calcium oxide and methanol, adding divalent cobalt salt to form a homogeneous solution, then stirring in an inert atmosphere, and finally centrifuging, washing and drying to obtain nanodisks.

Benefits of technology

The efficient preparation of hierarchical porous Co(OH)2 nanodisks based on waste biomass was achieved, providing a new preparation method for two-dimensional transition metal nanomaterials, and the material has strong resistance to organic pollutants such as rhodamine B. Efficient degradation ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116395755B_ABST
    Figure CN116395755B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a hierarchical porous Co(OH)2 nanodisk using calcium oxide as a precursor, and belongs to the field of material technology. The method uses calcium oxide as a precursor, and fully reacts with methanol under nitrogen protection to obtain a reaction intermediate calcium methanolate, and then adds a methanol solution of cobalt chloride hexahydrate, and then undergoes ion exchange, centrifugation, washing, and freeze drying to obtain a hierarchical porous Co(OH)2 nanodisk. The invention has a simple preparation process and can be mass-produced industrially. The obtained hierarchical porous Co(OH)2 nanodisk can quickly degrade organic pollutants such as RhB, and has good economic and environmental benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of material technology and specifically relates to a hierarchical porous Co(OH) 2 Preparation method of nanodisks and their applications. Background Art

[0002] With the improvement of living standards, a large amount of egg shells, oyster shells, etc. are discarded, which has caused serious environmental problems. Although some researchers have conducted simple research and utilization of these shells, they have not been able to achieve efficient comprehensive utilization. As a type of structurally adjustable two-dimensional material, two-dimensional transition metal hydroxides are often prepared under homogeneous conditions and rarely under heterogeneous conditions. To solve this bottleneck problem, the present invention designs a simple heterogeneous synthesis method to achieve hierarchical porous Co(OH) based on calcium oxide. 2 The preparation of nanodisks provides a new strategy for the preparation of two-dimensional transition metal hydroxide nanomaterials and the recycling of biomass shells, which is of great significance. Summary of the invention

[0003] The purpose of the present invention is to provide a hierarchical porous Co(OH) 2 Preparation method of nanodisks.

[0004] To achieve the above object, the present invention adopts the following technical solution:

[0005] A hierarchical porous Co(OH) 2 The nanoplate, the preparation method thereof comprises the following steps:

[0006] 1) Grind calcium oxide and add it to methanol, and stir it thoroughly under an inert atmosphere to prepare a uniformly dispersed reaction precursor solution;

[0007] 2) Add divalent cobalt salt to methanol, mix and dissolve thoroughly to prepare a uniformly dispersed homogeneous solution;

[0008] 3) adding the homogeneous solution obtained in step 2) to the reaction precursor solution obtained in step 1), and continuously stirring the mixture under an inert atmosphere to prepare a heterogeneous solution;

[0009] 4) The obtained heterogeneous solution is centrifuged, washed, and dried to obtain the hierarchical porous Co(OH) 2 Nanodisc.

[0010] Furthermore, the calcium oxide in step 1) is derived from biomass calcium or synthetic calcium oxide.

[0011] The method for preparing calcium oxide using biomass calcium is to wash, dry and calcine the biomass calcium; the biomass calcium is egg shell, clam shell or oyster shell; the drying temperature is 80°C and the time is 2-6 h; the calcination heating rate is 5-20°C / min, the temperature is 1000-1500°C and the time is 30-180min.

[0012] Furthermore, in step 1), the powder is ground to a size of 100 mesh.

[0013] Furthermore, the ratio of calcium oxide to methanol used in step 1) is 0.1-5.0 g:150-500 ml.

[0014] Furthermore, the inert gas used in step 1) is nitrogen.

[0015] Furthermore, the sufficient stirring in step 1) is specifically magnetic stirring at a speed of 500-1000 rpm for 6-72 h.

[0016] Furthermore, the divalent cobalt salt in step 2) is specifically cobalt chloride hexahydrate (CoCl 2 6H 2 O).

[0017] Furthermore, the ratio of the divalent cobalt salt to methanol used in step 2) is 0.5-25.0 g:100-300 ml.

[0018] Furthermore, the sufficient mixing and dissolving in step 2) is specifically carried out by magnetic stirring at a speed of 500-1000 rpm for 30-60 min.

[0019] Furthermore, the amount of the homogeneous solution and the reaction precursor solution used in step 3) is converted according to the molar ratio of the divalent cobalt salt to the reaction precursor being 10:1-1:10.

[0020] Furthermore, the sufficient stirring in step 3) is specifically magnetic stirring at a speed of 500-1000 rpm for 6-72 h.

[0021] Furthermore, in step 4), the centrifugation speed is 8000 rpm and the time is 3-5 min.

[0022] Furthermore, in step 4), the washing is performed by washing with ethanol and deionized water three times each.

[0023] Furthermore, the drying in step 4) is specifically freeze-drying at -53°C under vacuum conditions for 6-12 h.

[0024] The obtained hierarchical porous Co(OH) 2The nanodiscs can quickly and efficiently activate persulfate (PMS) to produce a large amount of singlet oxygen, which makes them useful for the degradation of various organic pollutants such as rhodamine B.

[0025] The present invention uses calcium oxide (CaO) as a precursor and nitrogen as a protective gas to convert calcium oxide into a hexagonal calcium methoxide template in a methanol solution, and then exchanges it with cobalt ions to prepare a hexagonal disc-shaped hierarchical porous Co(OH) 2 Nanomaterials.

[0026] The present invention provides a hierarchical porous Co(OH) 2 A green synthesis method for nanodisks is simple, low-cost, and the resulting hierarchical porous Co(OH) 2 The nanodisks have extremely high degradation activity against organic pollutants such as RhB and can be produced and applied on a large scale with good economic and environmental benefits.

[0027] The beneficial effects of the present invention are:

[0028] (1) The present invention adopts a heterogeneous method to realize the hierarchical porous Co(OH) 2 Preparation of nanodisks, which provide a new Co(OH) 2 The synthesis method provides new ideas for the preparation of two-dimensional porous transition metal nanomaterials and the efficient utilization of waste biomass calcium carbonate.

[0029] (2) Hierarchical porous Co(OH) prepared by the present invention 2 The nanomaterial has a regular hexagonal structure with a single particle size of about 800 nm and tiny nanosheets on the edges.

[0030] (3) The raw materials and equipment required for the preparation method of the present invention are simple and easy to obtain, the process is simple, easy to operate and safe, the cost is relatively low, and large-scale industrial production is possible; compared with the products prepared by other traditional methods, the hierarchical porous Co(OH) prepared by the present invention is 2 Nanodisc is an environmentally friendly new material with high degradation ability for rhodamine B, so it has great promotion and application value and use prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The hierarchical porous Co(OH) prepared in Example 1 2 Scanning electron microscopy (SEM) image of the nanodisk.

[0032] Figure 2 The hierarchical porous Co(OH) prepared in Example 1 2Transmission electron microscopy (TEM) image of the nanodisk.

[0033] Figure 3 The hierarchical porous Co(OH) prepared in Example 2 2 SEM image of the nanodisk.

[0034] Figure 4 The hierarchical porous Co(OH) prepared in Example 3 2 SEM image of the nanodisk.

[0035] Figure 5 The hierarchical porous Co(OH) prepared in Example 4 2 SEM image of the nanodisk.

[0036] Figure 6 This is the SEM image of the hierarchical porous MnOOH nanodisk prepared in Comparative Example 1.

[0037] Figure 7 This is the SEM image of the hierarchical porous FeOOH nanodisk prepared in Comparative Example 2.

[0038] Figure 8 This is the SEM image of the hierarchical porous Sr-Ca LDH nanomaterial prepared in Comparative Example 3.

[0039] Fig. 9 The hierarchical porous Ni(OH) prepared in Comparative Example 4 2 SEM images of nanomaterials.

[0040] Fig.10 The Ca(OH) prepared in Comparative Example 5 2 SEM images of the materials.

[0041] Fig.11 The hierarchical porous Co(OH) prepared in Example 1 2 X-ray diffraction (XRD) patterns of the nanodisks.

[0042] Fig.12 This is the X-ray diffraction (XRD) pattern of the hierarchical porous MnOOH nanodisk prepared in Comparative Example 1.

[0043] Fig.13 This is the X-ray diffraction (XRD) pattern of the hierarchical porous FeOOH nanodisk prepared in Comparative Example 2.

[0044] Fig.14 The hierarchical porous Ni(OH) prepared in Comparative Example 4 2 X-ray diffraction (XRD) patterns of nanomaterials.

[0045] Fig.15This is a comparison chart of the degradation rates of Rhodamine B by the nanomaterials prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 4.

[0046] Fig.16 The hierarchical porous Co(OH) prepared in Example 1 2 Comparison of the degradation rates of rhodamine B by nanodisks and commercial cobalt hydroxide.

[0047] Fig.17 The hierarchical porous Co(OH) prepared in Example 1 2 Performance diagram of the nanodisk subjected to cycling experiments. DETAILED DESCRIPTION

[0048] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined as long as they do not conflict with each other.

[0049] Example 1 Hierarchical Porous Co(OH) 2 Preparation of nanodiscs:

[0050] (1) Wash the eggshells, dry them at 80 °C for 6 h, and then calcine them at a heating rate of 5 °C / min from room temperature to 1050 °C for 1 h.

[0051] (2) Grind the calcined eggshells in a mortar and weigh 0.56 g using an electronic balance and add it to a three-necked flask, then add 150 ml of methanol;

[0052] (3) Then, under the condition of nitrogen as the protective gas, the mixed solution was magnetically stirred at a speed of 750 rpm for 24 h to obtain a uniform heterogeneous solution A;

[0053] (4) Use an electronic balance to weigh 2.38 g of cobalt chloride hexahydrate (CoCl 2 6H 2 O), add 100 ml of methanol, stir magnetically at 750 rpm for 45 min, and mix to form a uniform solution B;

[0054] (5) The homogeneous solution B was added to the heterogeneous solution A, and the mixture was magnetically stirred at 750 rpm for 24 h under a nitrogen atmosphere. The mixture was then centrifuged at 8000 rpm for 4 min to obtain a precipitate. The precipitate was washed three times with ethanol and three times with deionized water, and freeze-dried at -53 °C under vacuum for 8 h to obtain a hierarchical porous Co(OH) 2 Nanodisc.

[0055] Example 2 Hierarchical Porous Co(OH) 2 Preparation of nanodiscs:

[0056] (1) Wash the oyster shells, dry them at 80 °C for 6 h, and then calcine them at a heating rate of 5 °C / min from room temperature to 1050 °C for 1 h.

[0057] (2) Grind the calcined oyster shells with a mortar and weigh 0.56 g with an electronic balance and add it to a three-necked flask, then add 150 ml of methanol;

[0058] (3) Then, under the condition of nitrogen as the protective gas, the mixed solution was magnetically stirred at a speed of 750 rpm for 24 h to obtain a uniform heterogeneous solution A;

[0059] (4) Use an electronic balance to weigh 2.38 g of cobalt chloride hexahydrate (CoCl 2 6H 2 O), add 100 ml of methanol, stir magnetically at 750 rpm for 45 min, and mix to form a uniform solution B;

[0060] (5) The homogeneous solution B was added to the heterogeneous solution A, and the mixture was magnetically stirred at 750 rpm for 24 h under a nitrogen atmosphere. The mixture was then centrifuged at 8000 rpm for 4 min to obtain a precipitate. The precipitate was washed three times with ethanol and three times with deionized water, and freeze-dried at -53 °C under vacuum for 8 h to obtain a hierarchical porous Co(OH) 2 Nanodisc.

[0061] Example 3 Hierarchical Porous Co(OH) 2 Preparation of nanodiscs:

[0062] (1) Wash the clam shells, dry them at 80 °C for 6 h, and then calcine them at a heating rate of 5 °C / min from room temperature to 1050 °C for 1 h.

[0063] (2) Grind the calcined clam shells with a mortar and weigh 0.56 g with an electronic balance and add it to a three-necked flask, then add 150 ml of methanol;

[0064] (3) Then, under the condition of nitrogen as the protective gas, the mixed solution was magnetically stirred at a speed of 750 rpm for 24 h to obtain a uniform heterogeneous solution A;

[0065] (4) Use an electronic balance to weigh 2.38 g of cobalt chloride hexahydrate (CoCl 2 6H 2 O), add 100 ml of methanol, stir magnetically at 750 rpm for 45 min, and mix to form a uniform solution B;

[0066] (5) The homogeneous solution B was added to the heterogeneous solution A, and the mixture was magnetically stirred at 750 rpm for 24 h under a nitrogen atmosphere. The mixture was then centrifuged at 8000 rpm for 4 min to obtain a precipitate. The precipitate was washed three times with ethanol and three times with deionized water, and freeze-dried at -53 °C under vacuum for 8 h to obtain a hierarchical porous Co(OH) 2 Nanodisc.

[0067] Example 4 Hierarchical Porous Co(OH) 2 Preparation of nanodiscs:

[0068] (1) Use an electronic balance to weigh 0.56 g of commercial calcium oxide and add it to a three-necked flask, then add 150 ml of methanol;

[0069] (2) Then, under the condition of nitrogen as the protective gas, the mixed solution was magnetically stirred at a speed of 750 rpm for 24 h to obtain a uniform heterogeneous solution A;

[0070] (3) Use an electronic balance to weigh 2.38 g of cobalt chloride hexahydrate (CoCl 2 6H 2 O), add 100 ml of methanol, stir magnetically at 750 rpm for 45 min, and mix to form a uniform solution B;

[0071] (4) The homogeneous solution B was added to the heterogeneous solution A, and the mixture was magnetically stirred at 750 rpm for 24 h under a nitrogen atmosphere. The mixture was then centrifuged at 8000 rpm for 4 min to obtain a precipitate. The precipitate was washed three times with ethanol and three times with deionized water, and freeze-dried at -53 °C under vacuum for 8 h to obtain a hierarchical porous Co(OH) 2 Nanodisc.

[0072] Comparative Example 1 Preparation of hierarchical porous MnOOH nanodisks:

[0073] (1) Wash the eggshells, dry them at 80 °C for 6 h, and then calcine them at a heating rate of 5 °C / min from room temperature to 1050 °C for 1 h.

[0074] (2) Grind the calcined eggshells in a mortar and weigh 0.56 g using an electronic balance and add it to a three-necked flask, then add 150 ml of methanol;

[0075] (3) Then, under the condition of nitrogen as the protective gas, the mixed solution was magnetically stirred at a speed of 750 rpm for 24 h to obtain a uniform heterogeneous solution A;

[0076] (4) Use an electronic balance to weigh 1.98 g of manganese chloride tetrahydrate (MnCl 2 ·4H 2O), add 100 ml of methanol, stir magnetically at 750 rpm for 45 min, and mix to form a uniform solution B;

[0077] (5) The homogeneous solution B was added to the heterogeneous solution A and magnetically stirred at 750 rpm for 24 h under a nitrogen atmosphere. The precipitate was then centrifuged at 8000 rpm for 4 min. The precipitate was washed three times with ethanol and three times with deionized water. It was freeze-dried at -53 °C under vacuum conditions for 8 h to obtain hierarchical porous MnOOH nanodisks.

[0078] Comparative Example 2 Preparation of hierarchical porous FeOOH nanodisks:

[0079] (1) Wash the eggshells, dry them at 80 °C for 6 h, and then calcine them at a heating rate of 5 °C / min from room temperature to 1050 °C for 1 h.

[0080] (2) Grind the calcined eggshells in a mortar and weigh 0.56 g using an electronic balance and add it to a three-necked flask, then add 150 ml of methanol;

[0081] (3) Then, under the condition of nitrogen as the protective gas, the mixed solution was magnetically stirred at a speed of 750 rpm for 24 h to obtain a uniform heterogeneous solution A;

[0082] (4) Use an electronic balance to weigh 1.99 g of ferrous chloride tetrahydrate (FeCl 2 ·4H 2 O), add 100 ml of methanol, stir magnetically at 750 rpm for 45 min, and mix to form a uniform solution B;

[0083] (5) The homogeneous solution B was added to the heterogeneous solution A and magnetically stirred at 750 rpm for 24 h under a nitrogen atmosphere. The precipitate was then centrifuged at 8000 rpm for 4 min. The precipitate was washed three times with ethanol and three times with deionized water. It was freeze-dried at -53 °C under vacuum conditions for 8 h to obtain hierarchical porous FeOOH nanodisks.

[0084] Comparative Example 3 Preparation of hierarchical porous Sr-Ca LDH nanomaterials:

[0085] (1) Wash the eggshells, dry them at 80 °C for 6 h, and then calcine them at a heating rate of 5 °C / min from room temperature to 1050 °C for 1 h.

[0086] (2) Grind the calcined eggshells in a mortar and weigh 0.56 g using an electronic balance and add it to a three-necked flask, then add 150 ml of methanol;

[0087] (3) Then, under the condition of nitrogen as the protective gas, the mixed solution was magnetically stirred at a speed of 750 rpm for 24 h to obtain a uniform heterogeneous solution A;

[0088] (4) Use an electronic balance to weigh 2.67 g of strontium chloride hexahydrate (SrCl 2 6H 2 O), add 100 ml of methanol, stir magnetically at 750 rpm for 45 min, and mix to form a uniform solution B;

[0089] (5) The homogeneous solution B was added to the heterogeneous solution A, and the mixture was magnetically stirred at 750 rpm for 24 h under a nitrogen atmosphere. The mixture was then centrifuged at 8000 rpm for 4 min to obtain a precipitate. The precipitate was washed three times with ethanol and three times with deionized water, and freeze-dried at -53 °C under vacuum conditions for 8 h to obtain Sr-Ca LDH nanomaterials.

[0090] Comparative Example 4: Graded Porous Ni(OH) 2 Preparation of Nanomaterials:

[0091] (1) Wash the eggshells, dry them at 80 °C for 6 h, and then calcine them at a heating rate of 5 °C / min from room temperature to 1050 °C for 1 h.

[0092] (2) Grind the calcined eggshells in a mortar and weigh 0.56 g using an electronic balance and add it to a three-necked flask, then add 150 ml of methanol;

[0093] (3) Then, under the condition of nitrogen as the protective gas, the mixed solution was magnetically stirred at a speed of 750 rpm for 24 h to obtain a uniform heterogeneous solution A;

[0094] (4) Use an electronic balance to weigh 1.98 g of nickel chloride hexahydrate (NiCl 2 6H 2 O), add 100 ml of methanol, stir magnetically at 750 rpm for 45 min, and mix to form a uniform solution B;

[0095] (5) The homogeneous solution B was added to the heterogeneous solution A, and the mixture was magnetically stirred at 750 rpm for 24 h under a nitrogen atmosphere. The mixture was then centrifuged at 8000 rpm for 4 min to obtain a precipitate. The precipitate was washed three times with ethanol and three times with deionized water, and freeze-dried at -53 °C under vacuum for 8 h to obtain Ni(OH) 2 Nanomaterials.

[0096] Comparative Example 5Ca(OH) 2 Preparation of materials:

[0097] (1) Wash the eggshells, dry them at 80 °C for 6 h, and then calcine them at a heating rate of 5 °C / min from room temperature to 1050 °C for 1 h.

[0098] (2) Grind the calcined eggshells with a mortar and weigh 0.56 g with an electronic balance and add it to a three-necked flask, then add 150 ml of ethanol;

[0099] (3) Then, under the condition of nitrogen as the protective gas, the mixed solution was magnetically stirred at a speed of 750 rpm for 24 h to obtain a uniform heterogeneous solution A;

[0100] (4) Use an electronic balance to weigh 2.38 g of cobalt chloride hexahydrate (CoCl 2 6H 2 O), add 100 ml of ethanol, stir magnetically at 750 rpm for 45 min, and mix to form a uniform solution B;

[0101] (5) The homogeneous solution B was added to the heterogeneous solution A, and the mixture was magnetically stirred at 750 rpm for 24 h under a nitrogen atmosphere. The mixture was then centrifuged at 8000 rpm for 4 min to obtain a precipitate. The precipitate was washed three times with ethanol and three times with deionized water, and freeze-dried at -53 °C under vacuum for 8 h to obtain Ca(OH) 2 Material.

[0102] Figure 1 , 2 They are respectively the hierarchical porous Co(OH) prepared in Example 1 2 SEM and TEM images of the nanodisk. As can be seen from the figure, the obtained Co(OH) 2 The nanomaterial has a regular hexagonal structure with a particle size of about 800 nm, and its edges are assembled from tiny nanosheets.

[0103] Figure 3-9 The SEM images of the nanomaterials prepared in Examples 2-4 and Comparative Examples 1-4 are shown respectively. It can be seen from the figure that the preparation method proposed by the present invention has great universality of calcium source, and even commercial calcium oxide can be fully converted into the target product. Moreover, a regular hexagonal structure can be prepared for various metal ions.

[0104] Fig.10 The Ca(OH) prepared in Comparative Example 5 2 SEM image of the material. It can be seen from the image that cobalt hydroxide nanodisks cannot be obtained after replacing the solvent.

[0105] Figure 11-14The X-ray diffraction (XRD) comparison diagrams of the nanomaterials prepared in Example 1 and Comparative Examples 1, 2, and 4 are shown. It can be further seen from the figure that a variety of corresponding hydroxides can be prepared by using the template effect of calcium methoxide.

[0106] Application Example Organic Matter Degradation Experiment

[0107] The nanomaterials obtained in Example 1 and the comparative example are used to degrade organic matter, and the specific steps are as follows:

[0108] (1) Prepare 20 ppm rhodamine B solution and 1 M potassium persulfate (PMS) solution;

[0109] (2) Use a measuring cylinder to weigh 25 ml of Rhodamine B solution, add 1 mg of nanomaterial, and sonicate for 5 min;

[0110] (3) Take 20 μl of PMS solution and add it to the above solution;

[0111] (4) After the solution was placed for different treatment times, the UV absorbance of Rhodamine B in the solution was tested using a UV-visible spectrophotometer, and the removal rate of Rhodamine B was calculated.

[0112] Fig.15 The figure is a comparison of the degradation rates of rhodamine B by the nanomaterials prepared in Example 1 and Comparative Examples 1, 2 and 4. As can be seen from the figure, the hierarchical porous Co(OH) 2 The nanomaterial has the best degradation activity and can achieve complete degradation of rhodamine B within 10 s.

[0113] Fig.16 The hierarchical porous Co(OH) prepared in Example 1 2 Nanodiscs and commercial Co(OH) 2 Comparison of the degradation rates of Rhodamine B by materials. As can be seen from the figure, hierarchical porous Co(OH) 2 Nanomaterials can quickly activate PMS, thereby generating a large amount of singlet oxygen, which in turn exhibits excellent degradation performance for rhodamine B, while conventional Co(OH) 2 Since the material activates PMS at a slow rate, its degradation performance for rhodamine B is poor.

[0114] Fig.17 The hierarchical porous Co(OH) prepared in Example 1 2 The performance diagram of the nanodisk during the cyclic reaction. It can be seen from the figure that after 4 cycles, the hierarchical porous Co(OH) 2 The performance of the nanodisks did not significantly decrease, demonstrating their good reaction stability.

[0115] Those skilled in the art will easily understand that the above description is only a preferred example of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing hierarchical porous Co(OH)2 nanodisks, characterized in that: The following steps are involved: 1) Grind calcium oxide and add it into methanol, and stir it thoroughly under an inert atmosphere to prepare a reaction precursor solution; 2) Add divalent cobalt salt to methanol, mix and dissolve thoroughly to prepare a homogeneous solution; 3) adding the homogeneous solution obtained in step 2) to the reaction precursor solution obtained in step 1), and continuously and fully stirring under an inert atmosphere to prepare a heterogeneous solution; 4) centrifuging, washing and drying the obtained heterogeneous solution to obtain the hierarchical porous Co(OH)2 nanodisks; Step 2) The divalent cobalt salt is specifically cobalt chloride hexahydrate.

2. The method for preparing a hierarchical porous Co(OH)2 nanodisk according to claim 1, characterized in that: The sufficient stirring in step 1) is specifically magnetic stirring at a speed of 500-1000 rpm for 6-72 h.

3. The method for preparing a hierarchical porous Co(OH)2 nanodisk according to claim 1, characterized in that: Step 2) The thorough mixing and dissolving is specifically carried out by magnetic stirring at a speed of 500-1000 rpm for 30-60 min.

4. The method for preparing a hierarchical porous Co(OH)2 nanodisk according to claim 1, characterized in that: The amount of the homogeneous solution and the reaction precursor solution used in step 3) is converted according to the molar ratio of the divalent cobalt salt to the reaction precursor being 10:1-1:

10.

5. The method for preparing a hierarchical porous Co(OH)2 nanodisk according to claim 1, characterized in that: Step 3) The sufficient stirring is specifically magnetic stirring at a speed of 500-1000 rpm for 6-72 h.

6. The method for preparing a hierarchical porous Co(OH)2 nanodisk according to claim 1, characterized in that: Step 4) The drying is specifically freeze-drying at -53°C under vacuum conditions for 6-12 h.

7. A hierarchical porous Co(OH)2 nanodisk prepared by the method according to any one of claims 1 to 6.

8. Use of the hierarchical porous Co(OH)2 nanodisk as claimed in claim 7 in degrading organic pollutants.

Citation Information

Patent Citations

  • Preparation method and application of 0D / 2D composite calcium oxide metal oxide nano catalytic material

    CN111889104A

  • Alpha-phase nickel hydroxide as well as preparation method and application thereof

    CN114735764A